2022
DOI: 10.51542/ijscia.v3i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Profiles and Clinical Outcomes of Perforated Peptic Ulcer with Boey Score 3 Treated with External Drainage in Indonesia

Abstract: The treatment of peptic ulcers has changed substantially, and the rate of elective surgery for gastroduodenal peptic ulcers has fallen significantly; as a result, the rate of emergency surgery for perforated peptic ulcers has slightly increased. The Boey score is one of the most widely used prognostic scoring systems for predicting death in peptic ulcer perforation patients. The Boey scoring system has a positive connection with mortality risk. Patients with Boey Score 3 are patients who meet the high-risk cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is normally indicated in high-risk patients like those with a Boey score of 3, an ASA score of 4 or 5 and patients with multiple co-morbidities. The mortality is high in this patient and most studies have shown that this is a stop gap measure and is not widely practiced [56][57][58][59][60].…”
Section: Conservative Treatment Of Perforated Peptic Ulcermentioning
confidence: 99%
“…It is normally indicated in high-risk patients like those with a Boey score of 3, an ASA score of 4 or 5 and patients with multiple co-morbidities. The mortality is high in this patient and most studies have shown that this is a stop gap measure and is not widely practiced [56][57][58][59][60].…”
Section: Conservative Treatment Of Perforated Peptic Ulcermentioning
confidence: 99%